2017
DOI: 10.3390/f8110444
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Diameter Density Prediction with k-NN and Airborne Lidar

Abstract: While lidar-based forest inventory methods have been widely demonstrated, performances of methods to predict tree diameters with airborne lidar (lidar) are not well understood. One cause for this is that the performance metrics typically used in studies for prediction of diameters can be difficult to interpret, and may not support comparative inferences between sampling designs and study areas. To help with this problem we propose two indices and use them to evaluate a variety of lidar and k nearest neighbor (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
(26 reference statements)
2
15
0
Order By: Relevance
“…With respect to the performance of MSN and RF imputation for diameter distributions, it was found intuitively from Figure 5 that most of RF imputed distributions had higher accuracies than MSN among different response configurations, except that MSN performed slightly better than RF when the response configuration was SET1-2 for all plots, and SET4-5 and SET13-14 for Eucalypt. Similar to Strunk et al [35] and Shang et al [59], RF was fairly insensitive to the choice of response configurations and was more robust than MSN. As a robust method against overfitting, the superiority of RF for predicting forest structure attributes had been reported by previous studies [56,57,86,106].…”
Section: The Selection Of Number Of Neighbors Response Configurationsupporting
confidence: 60%
See 4 more Smart Citations
“…With respect to the performance of MSN and RF imputation for diameter distributions, it was found intuitively from Figure 5 that most of RF imputed distributions had higher accuracies than MSN among different response configurations, except that MSN performed slightly better than RF when the response configuration was SET1-2 for all plots, and SET4-5 and SET13-14 for Eucalypt. Similar to Strunk et al [35] and Shang et al [59], RF was fairly insensitive to the choice of response configurations and was more robust than MSN. As a robust method against overfitting, the superiority of RF for predicting forest structure attributes had been reported by previous studies [56,57,86,106].…”
Section: The Selection Of Number Of Neighbors Response Configurationsupporting
confidence: 60%
“…Another reason explaining these results may be the fact that RF has an iterative procedure and the average outcome does not describe the worst possible case [57], which may lead to a stable and robust predictive ability of RF for diameter distributions. However, a limitation of RF was that calculating distances is more time-consuming than MSN [35]. As shown in Figure 5, generally, we also found that there was no significant improvement in separate MSN imputations by tree species compared to the imputed diameter distributions for all plots, although there was a significant improvement in RF imputation (Figure 5b).…”
Section: The Selection Of Number Of Neighbors Response Configurationmentioning
confidence: 71%
See 3 more Smart Citations